Phantom testing of two clinical spatially-resolved NIRS instruments. Issue 3 (2005) - Macnab Macnab, A. J. A. J.; Gagnon Gagnon, R. E. R. E.
Abstract : We used a living biological phantom to evaluate whether previously observed clinical differences in data collection between two similar near infrared spectrophotometers were due to technical design differences. A Somanetics INVOS-5100 was compared to a Hamamatsu NIRO-300. Both express the ratio of oxygenated hemoglobin to total hemoglobin concentration as a percentage, and both are intended for monitoring cerebral oxygenation status at the bedside. The living phantom simulated different bone densities and contained a low haematocrit solution of blood, intra-lipid, and saline, to which was added grower's yeast to alter oxygenation status. Results: In all trials, oxygen saturation decreased from 100% to 0 % as the yeast consumed the available oxygen. In all trials the spectrometers were significantly correlated (range: r 2 =0.815 to 0.995, p 2 >0.232). The NIRO-300 indicated oxygenation change 1 minute after addition of yeast, whereas the INVOS-5100 showed change after 5 minutes. Simulated bone thickness had almost no effect upon the NIRO-300, but did affect the INVOS-5100. Conclusion: In this study, the spectrophotometers had similar results consistent with the technical design differences: the INVOS-5100 does not report hemoglobin saturation change above 95% or below 15% while the NIRO-300 reports the full range from 100% to 0%.